Activities of the Chair in prehistoric archaeology of the Department of Archaeology, University of Zadar (Archaeologia Adriatica, 2013)
A concise overview of the Chair in Prehistoric Archaeology of the former Faculty of Philosophy in Zadar, present-day University of Zadar, is given. Emphasis is placed on main achievements of excavations, with brief overview of each excavated site.
Keywords: Chair in Prehistoric Archaeology; Department of Archaeology; University of Zadar